Bioglass: A novel biocompatible innovation - Vidya Krishnan; T Lakshmi (Wolters Kluwer Medknow Publications, 2013)
Advancement of materials technology has been immense, especially in the past 30 years. Ceramics has not been new to dentistry. Porcelain crowns, silica fillers in composite resins, and glass ionomer cements have already been proved to be successful. Materials used in the replacement of tissues have come a long way from being inert, to compatible, and now regenerative. When hydroxyapatite was believed to be the best biocompatible replacement material, Larry Hench developed a material using silica (glass) as the host material, incorporated with calcium and phosphorous to fuse broken bones. This material mimics bone material and stimulates the regrowth of new bone material. Thus, due to its biocompatibility and osteogenic capacity it came to be known as "bioactive glass-bioglass." It is now encompassed, along with synthetic hydroxyapatite, in the field of biomaterials science known as "bioactive ceramics." The aim of this article is to give a bird's-eye view, of the various uses in dentistry, of this novel, miracle material which can bond, induce osteogenesis, and also regenerate bone.